Economic decision analysis - Fabrycky, W. J.; Thuesen, G. J. (Englewood Cliffs, N.J. : Prentice-Hall, 1974)
The book presents methods and techniques of analysis for optimizing the economic outcome of managerial decisions.
Includes bibliographical references: p. 383-384.
rpm 20/06/2017
Loans
Keywords: Decision making; Decision making $1 (BMathematical models.s; Capital investments; Management; Financial management $1 (BDecision makings